2015
DOI: 10.1007/s11356-015-4916-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood cholinesterase activity levels of farmers in winter and hot season of Mae Taeng District, Chiang Mai Province, Thailand

Abstract: Organophosphate and carbamate pesticides have been widely used by farmers for crop protection and pest control. Inhibition of acetylcholinesterase (AChE) in erythrocyte and butyrylcholinesterase (BChE) in plasma is the predominant toxic effect of organophosphate and carbamate pesticides. Mae Taeng District, Chiang Mai Province, is one of the large areas of growing vegetables and fruits. Due to their regular exposure to these pesticides, the farmers are affected by this toxicity. The objective of the study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…It is apparent that exposure to OPs or carbamates leads to poisoning via the overstimulations of signal transduction due to accumulation of ACh at the synapse [17]. The AChE and BChE activities in every group were in a similar range which was reported in Malaysian by Chan et al [18] This study also reported higher activities of both AChE and BChE than Hongsibsong et al who reported among vegetable growers in Thailand [19]. In this study, BChE activity in the three growers' groups was lower than that in nonfarm workers.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…It is apparent that exposure to OPs or carbamates leads to poisoning via the overstimulations of signal transduction due to accumulation of ACh at the synapse [17]. The AChE and BChE activities in every group were in a similar range which was reported in Malaysian by Chan et al [18] This study also reported higher activities of both AChE and BChE than Hongsibsong et al who reported among vegetable growers in Thailand [19]. In this study, BChE activity in the three growers' groups was lower than that in nonfarm workers.…”
Section: Resultssupporting
confidence: 62%
“…Most recent studies in Thailand have reported exposure to a single type of pesticide in single crops grown by farmers, such as urinary DAPs levels in rice [11] and chili [12] or general farmers [13]. Despite the fact that Thai farmers use multiple pesticides in multicrop cultivation, the biomarker of pesticide exposure is lacking in one community of agricultural area where several agricultural crops are grown.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with a study of Mecdad et al in (Al-Salheya farms, Zagazig), which found that exposed agricultural workers recorded reduction in ChE level 1284.2 ± 245U/ml versus non-exposed group 6768.8 (±446.029) U/ml [7]. Also a lot of studies in Tunisia [17], Nigeria [9], Thiland [18] and India were in accordance with our results [19]. In contrast with this study, studies of Ogut et al [20] and Sudjaroen [21] didn't observe any statistical significant difference between both groups as regard BuChE levels.…”
Section: Subjects and Methods Study Design And Settingssupporting
confidence: 90%
“…Soil is a major absorber of these pesticides that inadvertently, eventually enter higher trophic levels organisms by desorption, dissolution, diffusion, transpiration, and accumulation. These pesticides can act on the acetylcholinesterase enzyme that is reported to cause nerve malfunction and disruption of the reproductive system [9,10]. As biomarkers of OPPs in the human body, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) levels in blood samples from agricultural farmers at San Pa Tong and Mae Taeng district, Northern Thailand were lower than those in nonfarm workers [9,11] Besides, its mutagenicity, teratogenicity, and carcinogenicity have an adverse effect on humans.…”
Section: Introductionmentioning
confidence: 99%
“…These pesticides can act on the acetylcholinesterase enzyme that is reported to cause nerve malfunction and disruption of the reproductive system [9,10]. As biomarkers of OPPs in the human body, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) levels in blood samples from agricultural farmers at San Pa Tong and Mae Taeng district, Northern Thailand were lower than those in nonfarm workers [9,11] Besides, its mutagenicity, teratogenicity, and carcinogenicity have an adverse effect on humans. The intensive use of OPPs has been proved to pose a threat to children in rural area of Zhejiang, China [12].…”
Section: Introductionmentioning
confidence: 99%